The Seasons of COVID-19: understanding the mood of older adults in the UK through a barometer survey spanning 12 months. (17th December 2021) - Palmarini, Nicola; Mitchell, Alex; Hall, Lesley; McNaughton, James; Nixon, Charlotte
Abstract: The impact of COVID-19 on older adults has been analysed through different research approaches. However, with its sudden global spread, combined with uncertainty about which countermeasures would be employed, there was a lack of opportunity to systematically and continuously engage in a system of observing the moods of older adults forced to live in unexpected conditions. Ageist narratives, social distancing, the unending barrage of real and fake news, and the lockdowns, have given rise to what we define as a series of "seasons" of life, characterised not by the weather barometer, but by moods of people. How much did these external events, like the impact of weather, affect the mood of older adults? We immediately recognised the pandemic's long-term nature, and thanks to our position as an "observatory" of social dynamics, and because of our existing community of older adults (VOICE), we could involve our members to provide valuable insights about mood and wellbeing during the pandemic. We initiated a weekly pulse survey, based on the two same questions, starting in week 13 of 2020. Across the 50 weeks which followed, we received 2577 responses. They rated their mood on a scale of 1 (extra-stormy) to 5 (all sunshine), before we collated the data and mapped on key events related to media announcements and political decisions. Our research showed the impact of these events on the mood of participants, and the potential of this approach to identify trends in mood to help policy makers with informed decision-making during unprecedented times.